Optimization of Digital-Based Library Services in MAN 1 Bulukumba: Optimalisasi Layanan Perpustakaan Berbasis Digital di MAN 1 Bulukumba - Sutamrin Sutamrin; Abdul Rahman; Rusli Rusli; Ansari Saleh Ahmar; Khadijah Khadijah (Yayasan Ahmar Cendekia Indonesia, 2022)
This Community Service is carried out by looking at the condition of the library's main books which are in disarray, the entry of books is not clear, lots of books are lost, whether they are borrowed, damaged, or for other reasons that are not clear, and many books are also destroyed without minutes so that an application is needed that can help the library to become more organized and monitored. The aim of PkM is to help optimize Digital-Based MAN 1 Bulukumba Library Services. PkM participants are librarians, teachers, and students of MAN 1 Bulukumba. The training implementation method consists of two stages, namely direct material presentation and mentoring, where material presentation is carried out in plenary and hands-on practice on how to install, introduce features and use them, and prospective library members also immediately try to open the application on their smartphone device. An analysis of the success of this PkM activity was carried out by observing the participants' ability to understand the material, the ability to use the application and the satisfaction of using the application, as well as the appearance of the application's features. The results of the activity were that this PkM succeeded in helping to optimize digital-based MAN 1 Bulukumba Library services. Participants are very able to understand the material and apply it in developing their library services such as being able to organize library books and Sistem Dewey Decimal Classification (DDC) are successfully implemented by classifying books according to their type and arranging the positions of these books so that they are easily found by library members. The ability to use applications by librarians is 100% because all library staff consisting of 4 librarians are able to provide library services through applications. Students and teachers who are prospective members of the library also managed to log in 100% to the MAN 1 Bulukumba Library application during the training. The satisfaction of the application users can be seen from the enthusiasm of the application users, and they have started to come and try to borrow books from the library. The development of display features and feature development is also very extraordinary. Librarians are able to adjust the appearance of features according to the identity of the school. There is a development of the barcode scan feature with a barcode that is made in each book and a notification feature via WhatsApp so that they can receive the latest information about borrowing their books. They can also transact using WhatsApp to extend the borrowing of books. Abstrak Pengabdian kepada Masyarakat (PkM) ini dilaksanakan dengan melihat kondisi buku induk perpustakaan yang amburadul, pencatatan buku masuk tidak jelas, banyak sekali buku-buku yang hilang, entah itu dipinjam, rusak, atau alasan lain yang tidak jelas, dan banyak juga buku dimusnahkan tanpa berita acara sehingga dibutuhkan suatu aplikasi yang dapat membantu perputakaan agar menjadi lebih terorganisir dan terpantau. Tujuan PkM yaitu untuk membantu Optimalisasi Layanan Perpustakaan MAN 1 Bulukumba Berbasis Digital. Peserta PkM yaitu pustakawan, guru, dan siswa-siswa MAN 1 Bulukumba. Metode pelaksanaan pelatihan terdiri atas dua tahapan yaitu pemaparan materi langsung dan pendampingan, dimana pemaparan materi dilakukan secara pleno dan paktek langsung bagaimana instalasi, pengenalan fitur-fitur dan penggunaannya, serta para calon anggota perpustakaan juga langsung mencoba membuka aplikasi di perangkat smartphone mereka. Analisis keberhasilan kegiatan PkM ini dilakukan dengan observasi kemampuan peserta memahami materi, kemampuan penggunaan aplikasi dan kepuasan penggunaan aplikasi, serta tampilan fitur aplikasi. Hasil kegiatan yaitu PkM ini berhasil membantu optimalisasi layanan Perpustakaan MAN 1 Bulukumba berbasis digital. Peserta sangat mampu memahami materi dan menerapkannya dalam mengembangkan pelayanan perpustakaannya seperti mampu mengorganisir buku-buku perpustakaan dan materi Sistem Dewey Decimal Classification (DDC) berhasil diterapkan dengan mengklasifikasikan buku sesuai dengan jenisnya dan mengatur posisi buku-buku tersebut agar mudah ditemukan oleh anggota perpustakaan. Kemampuan penggunaan aplikasi oleh pustakawan sudah 100% karena seluruh staf perpustakaan yang terdiri atas 4 orang pustakawan mampu memberikan pelayanan perpustakaan melalui aplikasi. Siswa dan guru yang menjadi calon anggota perpustakaan juga berhasil 100% login ke aplikasi Perpustakaan MAN 1 Bulukumba pada saat pelatihan. Untuk kepuasan pengguna aplikasi sendiri terlihat dari antusiasme pengguna aplikasi, dan sudah mulai berdatangan mencoba meminjam buku di perpustakaan. Perkembangan tampilan fitur dan pengembangan fitur juga sangat luar biasa. Pustakawan mampu menyesuaikan tampilan fitur sesuai dengan identitas sekolah. Ada pengembangan fitur scan barcode dengan barcode yang dibuat di setiap buku dan fitur notifikasi via whatsapp sehingga informasi terkini mengenai peminjaman buku mereka dapat mereka terima. Mereka juga dapat bertransaksi menggunakan whatsapp untuk perpanjangan peminjamam buku.